SEARCHING FOR 'YESTERDAY'S MAN' - CONNECTING HISTORICAL RESEARCH AND PROVERBIAL WISDOM* - Ilina Jakimovska (EtnoAntropoZum, 2016)
The article reviews the existing definitions of the proverbs, which is a genre of folk literature. It also examines the past and the contemporary relation between history and related scientific disciplines on the side and paremiology on the other. It presents a few examples of well known historical anthropological work in which the proverb is used as the only or as an additional research source. Finally, two Serbian proverbs that refer to political history of this nation are analysed.